Current possibilities of improving the results of kidney transplantation in patients of the older age group, including those with an aggravated urological history - B. Z. Khubutiya; O. N. Rzhevskaya; A. A. Lisenok (Трансплантология (Москва))
Introduction. All over the world and in Russia, the number of patients requiring dialysis therapy and kidney transplantation for chronic renal failure in the end-stage of the renal disease is increasing. In many countries of the world, the number of dialysis patients over 60 years of age accounts for 30 to 45% of all patients with chronic renal failure. Meantime, taking into account the improved methods for early diagnosis of chronic renal failure and the treatment methods for chronic kidney disease, including the renal replacement therapy, we can expect an increase in the number of elderly potential kidney transplant recipients. The likelihood of receiving a renal graft in elderly patients is significantly lower than in young recipients. Elderly patients are known to have a higher risk of death while waiting for a kidney transplant due to higher morbidity and lethality on dialysis. For this reason, the urgency of increasing the availability of kidney transplantation in elderly patients is growing over time. One of the solutions can be the use of kidneys from suboptimal donors with a far from ideal graft quality, but which could meet the needs for transplant care of the older age group of patients. The older age of a recipient entails a certain risk of developing a graft dysfunction due to the presence of concomitant diseases, and the potential risk increases even more with kidney transplants from expanded criteria donors. If a reduced functional reserve of kidneys removed from donors with extended criteria is identified, two-kidney transplantation is possible, which provides fairly good long-term results. To reduce the risk of a kidney graft loss, a careful selection of recipients is necessary, taking into account their co-morbidities, including the presence of urological diseases that impair the function of the upper and lower urinary tract. Their timely identification and correction makes it possible to raise the availability of kidney transplantation for elderly patients and improve its results. This review presents the results of the studies conducted in various world transplant centers, covers the mortality rates, kidney graft and recipient survival rates.The study purpose was to summarize the actual data and the results of the study on kidney transplantation in elderly patients with urological pathology.